Enhancing medical students comprehension through active learning: implementing the jigsaw method to improve engagement - Begum, Gulam; Goud, B. K. M.; Marakala, Vijaya; Hamad, Nasir A.; Elizabeth, Smitha; Khan, Farida H.; Agarwal, Anshoo; Khattak, Osama; Fareed, Muhammad Amber; Alshammari, Khalid F.; Desai, Vijay Bhavrao; Chaudhary, Farooq A. (Frontiers in Medicine, 2026)
ObjectiveThe Jigsaw method is an excellent collaborative learning strategy that actively involves students, improves their problem-solving abilities, and promotes individual accountability. This study investigated the effectiveness of the Jigsaw teaching and learning technique in enhancing medical students’ knowledge of nutrition, specifically focusing on fat-soluble vitamins and B complex vitamins in medical students.MethodsA descriptive, cross-sectional, and prospective study was conducted with 176 Biochemistry students (10 males, 166 females) pursuing a Doctor of Medicine (MD) degree. Participants were conveniently sampled. The Jigsaw activity centered on “Nutrition,” with subtopics including Vitamin A, Vitamin K, B complex (B1, B2, B6), and Biotin and Niacin.ResultsThe results showed across all four teams, mean scores for assignment, presentation, and expert-group activities were comparable, with total scores showing minimal variation. ANOVA demonstrated significant differences in Expert Group (F = 11.07, p < 0.001) and Assignment scores (F = 4.24, p = 0.006), while Presentation scores did not differ significantly (F = 1.08, p = 0.358). Pearson correlation analysis showed strong positive associations between assignment, presentation, and total scores, indicating consistent alignment of performance components across teams.ConclusionThe Jigsaw method proved effective in boosting student engagement, comprehension, and collaborative skills in complex Biochemistry topics. The study suggests that well-planned active teaching methods like the Jigsaw model can positively impact student learning and help achieve specific learning outcomes in medical education. Our study was limited to one institution; future multi-center, longitudinal and controlled studies are recommended to validate and expand these findings.